Accountability in education: the programme evaluation approach (2010)
Accountability and education are twins concepts in education. One cannot be divorced from the other. In fact the latter is the means to determin the former. As we have various types of accountability so there are many types of evaluation. The purpose of evaluation determines the type of evaluation on undertakes. However, the most effective type of accountability is programme evaluation, in the sense that it approaches accountability of any institution or programmes from the global or holistic perspective, assessing every segment of the programme to determine its performance ofr otherwise as well as its responsiveness to the environmental dynamics and its responsibility for the purpose of it establishing. Accountability enhances programme success. Hence the need for accountability in education cannot be overemphasized.